1986
DOI: 10.1128/jb.165.3.994-1001.1986
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of Bacillus stearothermophilus by protoplast fusion

Abstract: Efficient and reliable protoplasting, regeneration, and fusion techniques were established for the prototrophic strain Bacillus stearothermophilus NUB36. Auxotrophic mutants were isolated, and protoplast fusion was used to construct isogenic mutant strains and for chromosomal mapping. Markers were mapped using two-, threeP., and four-factor crosses. The order of the markers was hom-1-thr-1-his-1(gly-1 or gly-2)-pur-1-pur-2. These markers may be analogous to hom, thrA, hisA, glyC, and purA markers on the Bacilu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
0
30
0
Order By: Relevance
“…However, more recent measurements (Nazina et al, 2001) show that the G+C content for G. Group 6B includes NUB3621 (=BGSC 9A5), doubtless the most well-characterized Geobacillus strain from a genetic standpoint. Systems for plasmid transformation (Wu & Welker, 1989), generalized transduction (Welker, 1988) and protoplast fusion (Chen et al, 1986) have been described for this strain, and data generated from those studies have revealed a circular genetic map (Vallier & Welker, 1990). Although the research literature describes NUB3621 as G. stearothermophilus, the recN and 16S rRNA gene sequence analysis presented in Fig.…”
Section: Implications For Geobacillus Taxonomymentioning
confidence: 99%
“…However, more recent measurements (Nazina et al, 2001) show that the G+C content for G. Group 6B includes NUB3621 (=BGSC 9A5), doubtless the most well-characterized Geobacillus strain from a genetic standpoint. Systems for plasmid transformation (Wu & Welker, 1989), generalized transduction (Welker, 1988) and protoplast fusion (Chen et al, 1986) have been described for this strain, and data generated from those studies have revealed a circular genetic map (Vallier & Welker, 1990). Although the research literature describes NUB3621 as G. stearothermophilus, the recN and 16S rRNA gene sequence analysis presented in Fig.…”
Section: Implications For Geobacillus Taxonomymentioning
confidence: 99%
“…Aeromonas hydrophila RS61-6, Pseudomonas aeruginosa PA-3-11, Escherichia coli DH5aF', and B. subtilis BR151 were grown in Luria broth (LB) medium (Gibco BRL) at 37°C. Bacillus stearothermophilus NUB 3621 was grown at 65°C in LB medium supplemented with Castenholtz salts and trace elements as described by Chen et al (4). Haloferax volcanii DS2 was grown at 37°C in a yeast-tryptone-salts medium described by Nieuwlandt et al (23).…”
mentioning
confidence: 99%
“…The bacterial strains and plasmids used in this study are described in Table 1. B. stearothermophilus cultures were grown in modified Luria-Bertani (LB) medium (4), minimal glucose (MG) medium (4), and MG medium supplemented with 0.1% Bacto-Casamino Acids (Difco Laboratories, Detroit, Mich.) (MGCA medium). MG medium that did not contain NH4NO3 and nitrilotriacetate (nitrogen-free MG medium) was used in some experiments.…”
Section: Methodsmentioning
confidence: 99%